Clinic Practical Guides for Cerebrovascular Diseases - Miguel Angel Buergo Zuaznábar; Otman Fernández Concepción; Jesús Pérez Nellar; Gloria Lara Fernández; Carlos Maya Entenza; Alejandro Pando Cabrera (Medisur)
The clinic practical guides for cerebrovascular diseases are presented. They include different aspects as its concept, classification, and epidemiological data in Cuba as well as worldwide. They also offer its diagnosis, classification, complications and treatment. The frequency of assessment of its application including the tools to measure the quality of life in patients with cerebrovascular accident and the way to proceed with them are shown